Experience of Individual Northern European Countries in Providing Protection of Justice (Criminological Aspect and Criminal Law Aspect) - Khrystova, Yuliia; Khrystov, Oleksandr; Karpenko, Maksym; Shendryk, Vladyslav; Kasapohlu, Svitlana (Syariah: Jurnal Hukum dan Pemikiran, 2024)
The purpose of the article is to  describes experience of Denmark, Finland, Norway and Sweden in providing criminological protection of justice. . This article is the qualitative research with a historical and comparative approach. Thus, as of 01 January, 2023, employees of the Court Security Service in Ukraine ensured public order and security in 590 appellate and local courts and bodies of the justice system, which is more than 80% of their total number , and as of 01 January 2024 security was ensured in 639 (87 %) objects of the justice system.  To a large extent, this is related to introduction of restrictions in Ukraine provided for by martial law as a result of the armed aggression of the Russian Federation.The results of the study concluded that the  it has been established that  today in some countries of Northern Europe, in contrast to Ukraine, permanent security checks for all visitors are implemented only in those courts where such checks are needed for security reasons, and implementation of such a criminological function is entrusted to security inspectors represented by police officers, court employees, as well as security companies. Based on the results of the research, promising directions for improving activities of the Court Security Service of Ukraine were determined, and expediency of strategic planning practice in the sphere of ensuring protection of justice in Ukraine was also emphasized.